NURSING ASSISTANCE IN THE TREATMENT AND CARE OF VENOUS ULCER - Narciso de Oliveira, Alexsandro (Health and Society, 2023)
Venous ulcers constitute a serious public health problem, due to the large number of people affected by health care needs; cause absence from work or loss of employment, contributing to increase public spending, in addition to causing people’s suffering and interfering with their quality of life. The importance of adequate care for this population is considered, there is a need for a multidisciplinary team, in which nursing is inserted, which stands out for providing care, in the assessment of injuries, performing dressings, and in addition to these services also carrying out educational actions for a favorable evolution of the healing process and prevention of the appearance of possible injuries and recurrences.